PENINGKATAN PRODUKTIVITAS USAHA KERIPIK IKAN KUNIR UD FARAH DENGAN PENERAPAN TEKNOLOGI MESIN VACUUM FRYING SERTA MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA KARYAWAN - Mufarida, Nely Ana; Fitriana, Fitriana; Ridlo, Muhammad Zainur (Universitas Mataram, 2024)
Panarukan District, Situbondo Regency, has marine potential that supports marine fish-based processing industries, including UD FARAH in Paowan Village, a producer of turmeric fish chips. However, UD FARAH's production capacity is still low because it uses traditional equipment such as wood stoves. Technological development is needed to increase production efficiency and quality, which is expected to increase profits and meet growing market demand. The aim of this activity is to improve employee skills in operating Vacuum Frying Machines for the production of turmeric fish chips and strengthen their understanding of occupational safety and health (K3). UD FARAH faces traditional production problems which result in less than optimal product quality and quantity, as well as working conditions that do not meet K3 standards. Solutions include the application of Vacuum Frying Machine technology and K3 training to increase production efficiency and work safety. The program also includes mentoring and evaluation to ensure long-term success. After the service activities, UD FARAH experienced a significant increase in productivity and product quality with the implementation of the Vacuum Frying Machine. Employees' knowledge of technology and K3 also increases, which contributes to work safety and efficiency. In addition, the sustainability program includes marketing strategies and product diversification, such as the development of mango chips, which utilize local resources and open up new market opportunities. It is also hoped that the sustainability of this program will reduce UD FARAH's dependence on one type of product, increase competitiveness and create added value for the local community. This activity succeeded in improving the skills of UD FARAH employees in operating vacuum frying machines and implementing K3, as well as encouraging product diversification and improving marketing strategies to increase productivity and sales.